2000
DOI: 10.1002/(sici)1097-0193(200006)10:2<49::aid-hbm10>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

ERPs and PET analysis of time perception: Spatial and temporal brain mapping during visual discrimination tasks

Abstract: ERPs were recorded from 12 subjects performing duration and intensity visual discrimination tasks which have been previously used in a PET study. PET data showed that the same network was activated in both tasks [P. Maquet et al., NeuroImage 3:119-126, 1996]. Different ERP waveforms were observed for the late latency components depending on the dimension of the stimulus to be processed: frontal negativity (CNV) for the duration task and parieto-occipital positivity (P300) for the intensity task. Using BESA sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
83
3
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 32 publications
13
83
3
2
Order By: Relevance
“…This negativity is similar in distribution and amplitude to what has been described elsewhere (e.g., Macar & Vidal, 2004;Pouthas, Garnero, Ferrandez, & Renault, 2000;Roth, Ford, Lewis, & Kopell, 1976;Ruchkin, McCalley, & Glaser, 1977) as the contingent negative variation (CNV). Bendixen, Grimm, and Schröger (2006) pointed out that the CNV has been hypothesized to be composed of at least four distinct negativities: an early wave associated with warning signals; an anterior and central negativity related to motor programming; a stimulus preceding negativity that is largest over more posterior regions; and a timing component that, like the negativity related to motor programming, is largest at anterior and central electrodes.…”
Section: Discussionsupporting
confidence: 83%
“…This negativity is similar in distribution and amplitude to what has been described elsewhere (e.g., Macar & Vidal, 2004;Pouthas, Garnero, Ferrandez, & Renault, 2000;Roth, Ford, Lewis, & Kopell, 1976;Ruchkin, McCalley, & Glaser, 1977) as the contingent negative variation (CNV). Bendixen, Grimm, and Schröger (2006) pointed out that the CNV has been hypothesized to be composed of at least four distinct negativities: an early wave associated with warning signals; an anterior and central negativity related to motor programming; a stimulus preceding negativity that is largest over more posterior regions; and a timing component that, like the negativity related to motor programming, is largest at anterior and central electrodes.…”
Section: Discussionsupporting
confidence: 83%
“…Several imaging studies have shown participation of the SMA in other timing tasks such as visual or auditory rhythm discrimination (Schubotz et al, 2000) and duration discrimination (Pouthas et al, 2000;Rao et al, 2001;Ferrandez et al, 2003). This is close to but not coincident with the main area of activation during our temporal discrimination task, which was more anterior in the pre-SMA.…”
Section: Areas Specific To Temporal Discriminationsupporting
confidence: 63%
“…This slow potential shift might belong to the CNV family (e.g., Walter, Winter, Cooper, McCallum, & Aldridge, 1964). Among the processes that have been discussed to contribute to the CNVare the anticipation of a stimulus (e.g., Walter et al, 1964), the timing of the interval (e.g., Elbert, Ulrich, Rockstroh, & Lutzenberger, 1991;Macar & Besson, 1985;McAdam, 1967;Pouthas, Garnero, Ferrandez, & Renault, 2000;Ruchkin, McCalley, & Glaser, 1977; for a review, see Pouthas, 2003), and the preparation of a (motor) response (e.g., Birbaumer, Elbert, Canavan, & Rockstroh, 1990). Similar potential drifts following the cue have been reported in earlier temporal-orienting studies (Correa et al, 2006;Griffin et al, 2002;Lange et al, 2003;Miniussi et al, 1999;Sanders & Astheimer, 2008).…”
Section: P4mentioning
confidence: 56%